Longitudinal study on metabolic abnormalities and diabetes risk in normal-weight japanese adults - Huang, Cheng; Gao, Zhichao; Zhang, Yuhang; Li, Guofeng (Frontiers in Endocrinology, 2024)
Background: Diabetes is a significant global health concern, with a growing prevalence in Japan. Individuals with normal body mass index who are metabolically unhealthy exhibit an elevated risk of diabetes onset. Investigating the relationship between Metabolically Unhealthy Normal-weight (MUNW) status and the risk of diabetes in non-diabetic individual is vital for implementing early preventive strategies. Methods: Using data from the NAGALA cohort, This study categorized 8,194 Japanese adults based on the score of metabolic syndrome (MetS) components they possessed. Cox proportional hazards regression models and multivariate logistic regression were used to assess the relationship between MUNW and the risk of developing diabetes, with analyses stratified by age and sex. Results: During an average follow-up of 7.19 years, 123 participants (1.5%) were diagnosed with diabetes. Among the participants, 766 (9.35%) were classified as MUNW, and 157 (1.92%) as having MetS. Compared to those with no MetS components, individuals with 1, 2, and ≥3 MetS components had progressively higher adjusted hazard ratios (HRs) for developing diabetes, at 4.56, 8.79, and 25.16, respectively. Further stratified analysis revealed that men aged ≤40 years had the highest risk of developing diabetes. For men, the adjusted HRs for having 1, 2, and ≥3 MetS components were 5.61, 7.80, and 28.59, respectively, and for participants aged ≤40 years, the HRs were 12.31, 25.57, and 129.82, respectively. Conclusion: The prevalence of MUNW in non-diabetic individuals in Japan is 9.35%.The score of MetS components was positively correlated with the risk of diabetes. Early intervention and lifestyle modifications are crucial, especially for MUNW individuals and notably young Japanese men aged ≤40 years, for the prevention and management of diabetes.